(64-X^3).(5^X-25)=0.tìm x
Tìm x , biết :
a, x mũ 2 - 2x + 1 = 25
b, 4 x mũ 2 - ( x + 4 ) mũ 2 = 0
c, 9 - 64 x mũ 2 = 0
d, 9 ( 4 x + 3 ) mũ 2 = 16 ( 3 x - 5 ) mũ 2
a. x mũ 2 - 2x + 1 = 25
= x^2 + 2.x.1 + 1^2
= ( x + 1 ) ^2
ko bt có đúng ko nữa, mấy câu kia tui ko bt lm
bài 1 : Tìm x
a) 5 + ( x + 27 ) = 64
b) 64 - ( x - 2 ) = 25
c) 7 - ( x + 5 ) + 14 = 343
d) 5 . x - 25 = 10
e) 4 . ( x - 5 ) - 8 = 48
f) 49 - ( 15 + x ) = 12
g) 49 - 7. ( 13 - x ) = 14
h) 155 - 10. ( x + 1 ) = 55
5 + ( x + 27 ) = 64
( x + 27 ) = 64 - 5 ( x + 27 ) = 59 x = 59 - 27 x = 32a) \(\Rightarrow x+27=59\Rightarrow x=32\)
b) \(\Rightarrow x-2=39\Rightarrow x=41\)
c) \(\Rightarrow x+5=-322\Rightarrow x=-327\)
d) \(\Rightarrow5x=35\Rightarrow x=7\)
e) \(\Rightarrow4\left(x-5\right)=56\Rightarrow x-5=14\Rightarrow x=19\)
f) \(\Rightarrow15+x=37\Rightarrow x=22\)
g) \(\Rightarrow7\left(13-x\right)=35\Rightarrow13-x=5\Rightarrow x=8\)
h) \(\Rightarrow10\left(x+1\right)=100\Rightarrow x+1=10\Rightarrow x=9\)
Tìm x , biết :
a. 4x3 - 9x = 0
b. 3x(x - 2) - 5x + 10 = 0
c. 4x (x + 3) - x2 + 9 = 0
d. (2x + 5) (x - 4) = (x - 4) (5 - x)
e. 16x2 - 25 = (4x - 5) ( 2x + 1)
f. (x + 1/5)2 = 64/9
g. 9(x + 2)2 = (x + 3)2
a) \(4x^3-9x=0\)
\(\Leftrightarrow x\left(4x^2-9\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\4x^2=9\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\frac{3}{2}\end{cases}}\)
b) \(3x\left(x-2\right)-5x+10=0\)
\(\Leftrightarrow\left(3x-5\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=2\end{cases}}\)
c) \(4x\left(x+3\right)-x^2+9=0\)
\(\Leftrightarrow4x\left(x+3\right)-\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left(3x+3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-1\\x=-3\end{cases}}\)
d) \(\left(2x+5\right)\left(x-4\right)=\left(x-4\right)\left(5-x\right)\)
\(\Leftrightarrow\left(2x+5\right)\left(x-4\right)+\left(x-5\right)\left(x-4\right)=0\)
\(\Leftrightarrow3x\left(x-4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=4\end{cases}}\)
e) \(16x^2-25=\left(4x-5\right)\left(2x+1\right)\)
\(\Leftrightarrow\left(4x-5\right)\left(4x+5\right)-\left(4x-5\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left(4x-5\right)\left(2x+4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{4}\\x=-2\end{cases}}\)
f) \(\left(x+\frac{1}{5}\right)^2=\frac{64}{9}\)
\(\Leftrightarrow\orbr{\begin{cases}x+\frac{1}{5}=\frac{8}{3}\\x+\frac{1}{5}=-\frac{8}{3}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{37}{15}\\x=-\frac{43}{15}\end{cases}}\)
g) \(9\left(x+2\right)^2=\left(x+3\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}3x+6=x+3\\3x+6=-x-3\end{cases}}\Leftrightarrow\orbr{\begin{cases}2x=-3\\4x=-9\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-\frac{3}{2}\\x=-\frac{9}{4}\end{cases}}\)
Tìm x , biết :
a. 4x3 - 9x = 0
b. 3x(x - 2) - 5x + 10 = 0
c. 4x (x + 3) - x2 + 9 = 0
d. (2x + 5) (x - 4) = (x - 4) (5 - x)
e. 16x2 - 25 = (4x - 5) ( 2x + 1)
f. (x + 1/5)2 = 64/9
g. 9(x + 2)2 = (x + 3)2
Tìm x , biết :
a. 4x3 - 9x = 0
b. 3x(x - 2) - 5x + 10 = 0
c. 4x (x + 3) - x2 + 9 = 0
d. (2x + 5) (x - 4) = (x - 4) (5 - x)
e. 16x2 - 25 = (4x - 5) ( 2x + 1)
f. (x + 1/5)2 = 64/9
g. 9(x + 2)2 = (x + 3)2
a) 4x3 - 9x = 0
<=> x( 4x2 - 9 ) = 0
<=> x( 2x - 3 )( 2x + 3 ) = 0
<=> x = 0 hoặc 2x - 3 = 0 hoặc 2x + 3 = 0
<=> x = 0 hoặc x = ±3/2
b) 3x( x - 2 ) - 5x + 10 = 0
<=> 3x( x - 2 ) - 5( x - 2 ) = 0
<=> ( x - 2 )( 3x - 5 ) = 0
<=> x - 2 = 0 hoặc 3x - 5 = 0
<=> x = 2 hoặc x = 5/3
c) 4x( x + 3 ) - x2 + 9 = 0
<=> 4x( x + 3 ) - ( x2 - 9 ) = 0
<=> 4x( x + 3 ) - ( x - 3 )( x + 3 ) = 0
<=> ( x + 3 )[ 4x - ( x - 3 ) ] = 0
<=> ( x + 3 )( 4x - x + 3 ) = 0
<=> ( x + 3 )( 3x + 3 ) = 0
<=> x + 3 = 0 hoặc 3x + 3 = 0
<=> x = -3 hoặc x= -1
d) ( 2x + 5 )( x - 4 ) = ( x - 4 )( 5 - x )
<=> ( 2x + 5 )( x - 4 ) - ( x - 4 )( 5 - x ) = 0
<=> ( x - 4 )[ ( 2x + 5 ) - ( 5 - x ) ] = 0
<=> ( x - 4 )( 2x + 5 - 5 + x ) = 0
<=> ( x - 4 ).3x = 0
<=> x - 4 = 0 hoặc 3x = 0
<=> x = 4 hoặc x = 0
e) 16x2 - 25 = ( 4x - 5 )( 2x + 1 )
<=> ( 4x - 5 )( 4x + 5 ) - ( 4x - 5 )( 2x + 1 ) = 0
<=> ( 4x - 5 )[ ( 4x + 5 ) - ( 2x + 1 ) ] = 0
<=> ( 4x - 5 )( 4x + 5 - 2x - 1 ) = 0
<=> ( 4x - 5 )( 2x + 4 ) = 0
<=> 4x - 5 = 0 hoặc 2x + 4 = 0
<=> x = 5/4 hoặc x = -2
f) ( x + 1/5 )2 = 64/9
<=> ( x + 1/5 )2 = ( ±8/3 )2
<=> x + 1/5 = 8/3 hoặc x + 1/5 = -8/3
<=> x = 37/15 hoặc x = -43/15
g) 9( x + 2 )2 = ( x + 3 )2
<=> 32( x + 2 )2 - ( x + 3 )2 = 0
<=> [ 3( x + 2 ) ]2 - ( x + 3 )2 = 0
<=> ( 3x + 6 )2 - ( x + 3 )2 = 0
<=> [ ( 3x + 6 ) - ( x + 3 ) ][ ( 3x + 6 ) + ( x + 3 ) ] = 0
<=> ( 3x + 6 - x - 3 )( 3x + 6 + x + 3 ) = 0
<=> ( 2x + 3 )( 4x + 9 ) = 0
<=> 2x + 3 = 0 hoặc 4x + 9 = 0
<=> x = -3/2 hoặc x = -9/4
Tìm các số nguyên x, biết: a) 8 . x = 64; b) (-5) . x = 25; c) 4. x +1 = 21; a) (-3) . x - 1 = 8;
Tìm các số nguyên x, biết:
a) 8 . x = 64;
b) (-5) . x = 25;
c) 4. x +1 = 21;
d) (-3) . x - 1 = 8.
a) x = 8.
b) x = -5.
c) x = 5.
d) x = -3.
Tìm x
a) 27x3 + 64 =0
b) -x2 -25 + 10x
a,\((3x)^3\)=-64(=)3x=-4(=)x=\(-\frac{4}{3}\)
ý b thiếu đề bài
a)\(27x^3+64=0\)
\(\Rightarrow27x^3=-64\)
\(\Rightarrow x^3=-\frac{64}{27}\)
\(\Rightarrow x^3=\left(-\frac{4}{3}\right)^3\)
\(\Rightarrow x=-\frac{4}{3}\)
Tìmx,y biết x^2-25=0 b, (x+1)^2=4 c, (x-3)^3-64=0 d, 2^x+1-128=0 e, x^2 +(y-2)^2=0
a: =>(x-5)(x+5)=0
=>x=5 hoặc x=-5
b: \(\Leftrightarrow\left[{}\begin{matrix}x+1=2\\x+1=-2\end{matrix}\right.\Leftrightarrow x\in\left\{1;-3\right\}\)
c: =>x-3=4
hay x=7
d: =>x+1=7
hay x=6
e: =>x=0 và y-2=0
hay x=0 và y=2